Rethinking corporate social responsibility in the mining industry: focusing on recipients' perspectives - Hlatshwayo, Thina M (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
Views on the importance of companies engaging in CSR initiatives have been debated widely and critics of the concept continue to argue both locally and globally. The objective of the study was to gain an in-depth understanding of the recipients' perspectives on their involvement in CSR projects implemented in their community by a chosen mining company and the successes and challenges of the project. A qualitative research approach was used for the study. Using nonprobability purpose sampling, a total of 15 participants from Lusikisiki were selected for the study. The data obtained was analysed using inductive thematic analysis. The results of the study were discussed based on the three research questions of the study which focused on recipients' perspectives on their involvement in the projects and their perceptions on the successes and challenges of the projects. The study found that the chosen mining company made a significant contribution towards developing the community. Furthermore, the study found that recipients' involvement in the projects enabled them to realize their assets in one of the projects as a result of the shift in approach by the organisation as the project progressed (Needs Based Approach to ABCD Approach). In addition, the study found that the successes of the projects changed the recipients' perceptions of themselves and enabled them to actively engage in transforming their lives. However, the projects did face many challenges and recipients posited that more still needs to be done by organisations to develop communities and ensure that projects remain sustainable long after their partnership has dissolved.
Keywords: Social responsibility of business -- South Africa -- Case studies; Mining industries -- Social aspects-- -- South Africa; Sustainable developmenet -- Social aspects -- South Africa